Maternal breastfeeding is associated with offspring microbiome diversity; a secondary analysis of the MicrobeMom randomized control trial - Yelverton, Cara A.; Killeen, Sarah Louise; Feehily, Conor; Moore, Rebecca L.; Callaghan, Shauna L.; Geraghty, Aisling A.; Byrne, David F.; Walsh, Calum J.; Lawton, Elaine M.; Murphy, Eileen F.; Van Sinderen, Douwe; Cotter, Paul D.; et al. (Frontiers in Microbiology, 2023)
Background Microbial dysbiosis in infancy can influence long-term health outcomes such as childhood obesity. The aim of this study is to explore relationships among maternal well-being during pregnancy, breastfeeding, and the infant gut microbiome. Methods This is a secondary analysis of healthy pregnant women from the MicrobeMom study, a double-blind randomized control trial of maternal probiotic supplementation (Bifidobacterium breve 702258) versus placebo antenatally and up to 3 months postpartum. Maternal well-being was assessed using the WHO-5 well-being index at 16 weeks’ and 34 weeks’ gestation. Breastfeeding practices were recorded at discharge from hospital and at 1 month postpartum. Infant stool samples were obtained at 1 month of age. Next generation shotgun sequencing determined infant microbial diversity. Independent sample t-tests and Mann-Whitney U tests informed adjusted regression analysis, which was adjusted for delivery mode, antibiotics during delivery, maternal age and body mass index (BMI), and probiotic vs. control study group. Results Women (n = 118) with at least one measure of well-being were on average 33 years (SD 3.93) of age and 25.09 kg/m2 (SD 3.28) BMI. Exclusive breastfeeding was initiated by 65% (n = 74). Any breastfeeding was continued by 69% (n = 81) after 1 month. In early and late pregnancy, 87% (n = 97/111) and 94% (n = 107/114) had high well-being scores. Well-being was not associated with infant microbial diversity at 1 month. In adjusted analysis, exclusive breastfeeding at discharge from hospital was associated with infant microbial beta diversity (PC2; 0.254, 95% CI 0.006, 0.038). At 1 month postpartum, any breastfeeding was associated with infant microbial alpha diversity (Shannon index; −0.241, 95% CI −0.498, −0.060) and observed species; (−0.325, 95% CI −0.307, −0.060), and infant microbial beta diversity (PC2; 0.319, 95% CI 0.013, 0.045). Exclusive breastfeeding at 1 month postpartum was associated with infant alpha diversity (Shannon index −0.364, 95% CI −0.573, −0.194; Simpson index 0.339, 95% CI 0.027, 0.091), and infant’s number of observed microbial species (−0.271, 95% CI −0.172, −0.037). Conclusion Breastfeeding practices at 1 month postpartum were associated with lower microbial diversity and observed species in infants at 1 month postpartum, which is potentially beneficial to allow greater abundance of Bifidobacterium. Clinical trial registration ISRCTN53023014.